URGENSI MEMAHAMI BAHASA ARAB BERBASIS HADIS DENGAN MENGGUNAKAN METODE TEMATIK - Putra, Eka Mahendra; Yahya, Muhammad; Ilyas, Abustani (DIRAYAH : Jurnal Ilmu Hadis, 2025)
Arabic, as a lingua sacra for Muslims, holds a distinct position due to its role as the medium for the revelation of the Qur'an and the Sunnah of Prophet Muhammad ﷺ. Authentic understanding of the Qur'an and Sunnah heavily relies on proficiency in Arabic. Linguistic limitations can hinder access to deep meanings, rhetorical beauty, and the essence of Islamic teachings. Without Arabic, reliance on translations risks misinterpretation. The history of Islamic civilization demonstrates Arabic's central role as the lingua franca of knowledge. However, in the digital era, the urgency of Arabic is threatened by the dominance of international languages, potentially eroding a profound and holistic understanding of Islam. This research is library research with qualitative approach. The purpose of the research is to understand Arabic from a hadith perspective, particularly the hadith about Qur'an reciters whose recitation does not go beyond their throats. This hadith criticizes shallow religious formalism and emphasizes the significance of internalizing meaning. Learning Arabic is a fundamental necessity for understanding, practicing, and preserving the intellectual heritage of Islam.